Conjunctive use of reclaimed water and groundwater in crop rotations - Al Khamisi, S. A.; Prathapar, Sanmugam A.; Ahmed, M. (Elsevier, 2013)
Irrigated agriculture in Oman relies solely on groundwater and Aflaj (Falaj is a canal system, which provides water for a community of farmers for domestic and agricultural use). With the increasing scarcity of freshwater available to agriculture, the need to use of reclaimed water (RW) from Sewage Treatment Plants (STP) in agriculture has increased. In this study, we explored how RW from an STP can be used directly, without Aquifer Storage and Recovery, as a source of irrigation water in conjunction with groundwater for agriculture. Average data from Muscat, Oman in the years from 1996 to 2010 was used for calculation of crop water requirement. Wheat, cowpea and maize were chosen as crops to be grown in rotation through the year. Using RW irrigation conjunctively with groundwater cropping areas of wheat, cowpea and maize can be increased by 323, 250 and 318% respectively, against utilization RW only. Of the total irrigation requirement 57.6% was met with reclaimed water (RW) and 42.4% was met with groundwater (GW). Therefore, it is recommended that decision makers should consider piping RW to areas where groundwater of good quality is available to conjunctively use and meet crop water requirements, rather than piping it to areas where groundwater is saline and unsuitable for irrigation. This will prevent disposal of RW to the sea and minimize stress on fresh groundwater zones.